Estimasi Waktu Untuk Pengadaan Material Berdasarkan Time Schedule Pada Proyek Pembangunan Ruko Kawasan SP Plaza Batu Aji - Wico Mindra Putra; Usmanul Hayadi Umar (Journal of Civil Engineering and Planning (JCEP), 2021)
The research aims to estimate the time for material procurement based on time schedule in Batu Aji SP Plaza Area. The method used in the determining the estimated time is conventional method in which the scheduling process is made in the form of a barchart to be more easily understood by readers and also makes scheduling more orderly and systematic. The estimated results of material procurement until arrived the project location is 15 days and the average real field procurement is 12 days, so it can be concluded that the material procurement process in the construction of Ruko Kawasan SP Plaza does not occure material delays for structural work, wall work and roof work.